Insider Insights : Building a Results-Based Management and Evaluation System in Colombia - Fernando Castro, Manuel (World Bank, Washington, DC, 2017)
Colombia's National Results-Based Management and Evaluation System (SINERGIA) is one of Latin America's outstanding results-based monitoring and evaluation initiatives. With 15 years of progressive development, SINERGIA has endured the countries' institutional, political, and fiscal problems and has attained one of the highest levels of development and customization in Latin America. Based on its accomplishments it has been held up as an example by multilateral organizations, donor agencies, and other governments. This paper examines the experience of institutionalizing Colombia's monitoring and evaluation (M&E) system, from the perspective of a former SINERGIA manager: Manuel Fernando Castro, Director of Public Policy Evaluation, and Department of National Planning. This study is meant to complement previous studies by other authors with an insider's account, description, and analysis of the obstacles encountered and the results obtained. Likewise, it presents recommendations on how to ensure further institutionalization and identifies several lessons that might be of interest to professionals who are developing evaluation systems in other countries.